DETERMINATION OF MANGIFERIN IN MANGIFERA INDICA L. STEM BARK EXTRACT (VIMANG®) AND PHARMACEUTICALS BY LIQUID CHROMATOGRAPHY - Gil, Eddy Castellanos; Hernández, Rolando González; Paz, Lauro Nuevas; Hoogmartens, Jos (Emirates Journal of Food and Agriculture, 2014)
A new liquid chromatography method for the analysis of mangiferin (I) from Mangifera indica L. stem bark extract (Vimang®), and pharmaceuticals is described. Screening experiments were performed by an experimental design to find the influence of some important chromatographic variables (methanol, column temperature and acetic acid) on the retention times and resolution between critical pairs in the separation. This design also permitted to estimate method robustness and optimal conditions to achieve the best resolution. The best separation was found using a LiChrospher RP 18, 5 µm, 250 x 4.6 mm I.D. column maintained at 25°C, a mobile phase comprising methanol-2.5% v/v aqueous solution of acetic acid (280:720, v/v) at a flow rate of 1.0 ml/min, and detection by UV at 254 nm. The method resolves I, the major component, from other components of the extract. The method showed good selectivity, repeatability (RSD < 2%) and linearity (r = 0.9998). The limits of detection and quantitation were 0.008% (0.9 ng) and 0.05% (6.2 ng), respectively, relative to a 0.6 mg/ml standard solution, injection volume 20 µl. This method was used to quantify I in some aqueous extracts from the natural product and pharmaceuticals.